Edukasi Masyarakat mengenai Perjanjian Perkawinan sebagai Bentuk Perlindungan Hukum bagi Pasangan Suami Istri - Mahmudah, Lifvia Lailatul (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Primary education about the separation of assets in a marriage agreement is an essential education for the community in building an ideal household. Although the marriage agreement is considered unnatural by most people, this provision is an act that is permitted by law in Indonesia. This study aims to determine public education regarding the Marriage Agreement as a form of legal protection for married couples. The research method used is normative juridical with a literature study approach. The study results show that the basic principles of marriage agreements in Indonesia are based on positive law and Islamic law. Its relevance is described in the Constitutional Court Decision Nomor 69/PUU-XIII/2015, and the Compilation of Islamic Law, which regulates the marriage agreement, is complementary and not contradictory. The conclusions in this study explain that basic education efforts regarding marriage agreements are important as an effort to manage a good household and avoid bad things.